Development of android-based self-assessment application for basic pencak silat techniques - Mukhti Fadhli Kurniawan; Nurul Ihsan; Roma Irawan; Aldo Naza Puta; Yovhandra Ockta (Research and Development in Education (RaDEn), 2024)
In Physical Education learning (PE), the absence of effective self-assessment to measure basic pencak silat techniques can hinder student learning and skill development. This research aimed to develop an Android-based self-assessment application for basic pencak silat techniques in PE classes. The study follows the Research and Development (R&D) method, incorporating the ADDIE model: Analysis, Design, Development, Implementation, and Evaluation. Through expert validation and field trials at State High School 1 Bengkalis, the application's feasibility and effectiveness were assessed. Results showed a high level of feasibility and effectiveness, with significant improvement in students' understanding and skills in basic pencak silat techniques. The application offers benefits such as ease of use for teachers, increased student interest, and clear learning objectives. However, challenges include dependence on internet connectivity and device limitations. Despite limitations, this study contributes to innovative and efficient learning aids, enhancing skill assessment in PE. The implications extend to curriculum integration and improved assessment methods for teachers, empowering students to monitor their progress and enhance their skills independently. Future research could explore broader applications in sports learning and address specific needs in pencak silat education.